Moving Beyond Pedagogy to Andragogy: Experimental Learning Exercises for Tourism/Hospitality Executive Training - Martin, D.; Woodside, Arch (Emerald Group Publishing Ltd., 2009)
Purpose – The purpose of this editorial is to introduce eight training exercises developed for tourism executive decision making. Design/methodology/approach – The paper introduces the papers in this special issue and discusses the need for experiential learning techniques for adult learners. Findings – It was found that applied learning exercises are more effective than cognitive learning experiences in adult education. Originality/value – The paper provides an introduction to experiential learning exercises for tourism and hospitality training.